Mechanisms of Oxidized LDL-Mediated Endothelial Dysfunction and Its Consequences for the Development of Atherosclerosis - Jiang, Hui; Zhou, Yongwen; Nabavi, Seyed M.; Sahebkar, Amirhossein; Little, Peter J.; Xu, Suowen; Weng, Jianping; Ge, Jianjun (Frontiers in Cardiovascular Medicine, 2022)
Atherosclerosis is an immuno-metabolic disease involving chronic inflammation, oxidative stress, epigenetics, and metabolic dysfunction. There is compelling evidence suggesting numerous modifications including the change of the size, density, and biochemical properties in the low-density lipoprotein (LDL) within the vascular wall. These modifications of LDL, in addition to LDL transcytosis and retention, contribute to the initiation, development and clinical consequences of atherosclerosis. Among different atherogenic modifications of LDL, oxidation represents a primary modification. A series of pathophysiological changes caused by oxidized LDL (oxLDL) enhance the formation of foam cells and atherosclerotic plaques. OxLDL also promotes the development of fatty streaks and atherogenesis through induction of endothelial dysfunction, formation of foam cells, monocyte chemotaxis, proliferation and migration of SMCs, and platelet activation, which culminate in plaque instability and ultimately rupture. This article provides a concise review of the formation of oxLDL, enzymes mediating LDL oxidation, and the receptors and pro-atherogenic signaling pathways of oxLDL in vascular cells. The review also explores how oxLDL functions in different stages of endothelial dysfunction and atherosclerosis. Future targeted pathways and therapies aiming at reducing LDL oxidation and/or lowering oxLDL levels and oxLDL-mediated pro-inflammatory responses are also discussed.